Endophytic actinobacteria from wild medicinal plants are a natural source of insecticide to control the African cotton leafworm (Spodoptera littoralis) - Mohamed K. Diab; Hala M. Mead; Mohamad A. Khedr; Mohamed S. Nafie; Abdelghafar M. Abu-Elsaoud; Amro Hanora; Sahar A. El-Shatoury (AMB Express, 2023)
Abstract Insecticide resistance in agricultural pests has prompted the need to discover novel compounds with new modes of action. We investigated the potency of secondary metabolites from seventy endophytic actinobacteria against laboratory and field strains of Spodoptera littoralis (fourth instar), comparable to the bioinsecticide spinetoram (Radiant SC 12%). Endophytes from Artemisia herba-alba and A. judaica were highly effective. Chemical profiling of the most potent metabolite of the strain Streptomyces sp. ES2 was investigated using LC-QTOF-MS-MS technique, and the activity was validated through molecular docking studies. Metabolic extracts from actinobacteria belonging to Streptomyces, Nocardioides, and Pseudonocardia showed immediate and latent death to the Spodoptera littoralis fourth instar larvae. The metabolite from strain ES2 has shown the most promising and significant histopathological and inhibitory effects on the fourth instar larvae. ES2 metabolite caused lesions in the body wall cuticle, indicating a different mode of action than that of Radiant. Chemical profiling of ES2 showed the presence of cyromazine (molt inhibitor), 4-nitrophenol, and diazinon as key constituents. In conclusion, these findings suggest that secondary metabolites from endophytic actinobacteria inhabiting wild medicinal plants can be a sustainable source for promising natural biocontrol agents. This is the first illustration of the insecticidal activity of Artemisia spp. microbiome, and natural cyromazine synthesis by actinobacteria.